A formal system for quantum communication environments - Araújo, Anderson de; Finger, Marcelo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2011)
The present paper provides a complete first-order system for quantum communication environments. These environments are static reliable synchronous systems of quantum communication among agents and the formal system defined combines probability and knowledge operators to describe them.